Psychological Factors of Tourist Expenditure: Neglected or Negligible? - Štefko, Róbert; Džuka, Jozef; Lačný, Martin (Frontiers in Psychology, 2022)
Despite recent progress in identifying the factors of tourist expenditure, knowledge of the psychological characteristics of tourists is necessary to fully understand their impact. Therefore, this study attempts to extend the economic, sociodemographic and trip-related factors by including psychological factors in the econometric models. A total of 1,036 Slovak tourists who paid for summer holidays abroad in the summer of 2021 were interviewed. Three of the six psychological factors analysed (two stable personality characteristics - conscientiousness and agreeableness as well as four tendencies expressing willingness to spend or save - spendthrift, tightwad, thrift and spending propensity) correlated significantly with the amount of expenditure. In addition to income, type of travel, children and duration of the stay, the results of the partial least squares test revealed the net effects of tightwad, spending propensity and thrift. The magnitude of the effects of psychological factors points to the need for further research.